China’s Health Diplomacy to ASEAN through ASEAN-China Comprehensive Strategic Partnership 2021-2025 - Kamila, Zahra Shaffa; Sari, Deasy Silvya (Journal of Strategic and Global Studies, 2026)
The world always faces limitations in dealing with the pandemic. China had emerged as an active actor in health diplomacy to address this. China was the first country to send vaccines and health aid to Southeast Asia through ASEAN. However, the relationship between China and ASEAN did not begin with the pandemic. Both countries have a long history and recently renewed their plan of action (POA), which serves as evidence of their relationship namely the ASEAN-China Comprehensive Strategic Partnership (CSP) 2021-2025. The POA includes a sub-chapter on health that navigates China's health diplomacy towards ASEAN. Therefore, this research aimed to examine China's health diplomacy towards ASEAN within the framework of the ASEAN-China CSP 2021-2025. This paper utilized the concepts of health diplomacy forms by Rudolf (2021), health diplomacy factors by Kickbusch (2013), and health diplomacy instruments by Bertorelli et al. (2013). This research used qualitative methods, with data collection process through official archives, documents, and internet-based research. This study found that China practiced health diplomacy towards ASEAN through two shapes: vaccine diplomacy and mask diplomacy. Factors in China's health diplomacy include: (i) joint action; (ii) the involvement of academics and scientists; (iii) the complexity of negotiations through hierarchical dialogue; (iv) alleviating equity issues regarding health in ASEAN; and (v) institutionalization features fulfilled through the ACCF. China's health diplomacy used operative and collaborative instrument realized through the consensus and implementation of the ASEAN-China CSP 2021-2025.